A House Divided Against Itself: Dostoevsky and the Psychology of Unbelief - Bullivant, Stephen (Literature and theology, 2008)
This is a study of Dostoevsky's writings in light of the work of several twentieth-century theologians who affirm the possibility of there being ‘pseudo-atheists, who believe that they do not believe in God but who unconsciously believe in Him’ (Maritain). In particular, the portrayals of three of his most famous atheist characters will be examined: Raskolnikov (Crime and Punishment), Kirillov (Demons) and Ivan Karamazov (The Brothers Karamazov). Despite these characters’ explicit unbelief, Dostoevsky's use of dreams, visions and gratuitous actions suggests that at a deeper level (that of their inner double) they possess a profound and insuperable faith in Christ. As will be demonstrated, this interpretation of them as ‘pseudo-atheists’ or ‘anonymous Christians’ both illumines Dostoevsky's religious thought, and has fruitful implications for modern theology.